2017
DOI: 10.1103/physrevmaterials.1.074602
|View full text |Cite
|
Sign up to set email alerts
|

Au-rich filamentary behavior and associated subband gap optical absorption in hyperdoped Si

Abstract: Au-hyperdoped Si, synthesized by ion implantation and pulsed laser melting, is known to exhibit a strong sub-band gap photoresponse that scales monotonically with the Au concentration. However, there is thought to be a limit to this behavior since ultrahigh Au concentrations (>1 × 10 20 cm −3) are expected to induce cellular breakdown during the rapid resolidification of Si, a process that is associated with significant lateral impurity precipitation. This work shows that the cellular morphology observed in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…In this regard, several studies have been reported focusing on the changes of optoelectronic properties upon thermal treatment. [ 41,45,55,61,67 ]…”
Section: Extended Room‐temperature Ir Photoresponse In Si Hyperdoped mentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, several studies have been reported focusing on the changes of optoelectronic properties upon thermal treatment. [ 41,45,55,61,67 ]…”
Section: Extended Room‐temperature Ir Photoresponse In Si Hyperdoped mentioning
confidence: 99%
“…The findings in the aforementioned works [ 45,55,58,61 ] suggest that a metastable local atomistic configuration of deep‐level impurity atoms in the Si host is responsible for the sub‐bandgap absorption. There is a one‐to‐one correlation between the substitutional deep‐level impurities and the unique properties.…”
Section: Extended Room‐temperature Ir Photoresponse In Si Hyperdoped mentioning
confidence: 99%
See 3 more Smart Citations